CCDC141 Mutations in Idiopathic Hypogonadotropic Hypogonadism - Turan, Ihsan (J Clin Endocrinol Metab, 2017)
CONTEXT: Gonadotropin-releasing hormone neurons originate outside the central nervous system in the olfactory placode and migrate into the central nervous system, becoming integral components of the hypothalamic-pituitary-gonadal axis. Failure of this migration can lead to idiopathic hypogonadotropic hypogonadism (IHH)/Kallmann syndrome (KS). We have previously shown that CCDC141 knockdown leads to impaired migration of GnRH neurons but not of olfactory receptor neurons. OBJECTIVE: The aim of this study was to further describe the phenotype and prevalence of CCDC141 mutations in IHH/KS. DESIGN: Using autozygosity mapping, candidate gene screening, whole-exome sequencing, and Sanger sequencing, those individuals carrying deleterious CDCD141 variants and their phenotypes were determined in a cohort of 120 IHH/KS families. PATIENTS AND INTERVENTIONS: No interventions were made. RESULTS: Our studies revealed nine affected individuals from four independent families in which IHH/KS is associated with inactivating CCDC141 variants, revealing a prevalence of 3.3%. Affected individuals (with the exception of those from family 1 who concomitantly have FEZF1 mutations) have normal olfactory function and anatomically normal olfactory bulbs. Four affected individuals show evidence of clinical reversibility. In three of the families, there was at least one more potentially deleterious variant in other known puberty genes with evidence of allelic heterogeneity within respective pedigrees. CONCLUSIONS: These studies confirm that inactivating CCDC141 variants cause normosmic IHH but not KS. This is consistent with our previous in vitro experiments showing exclusively impaired embryonic migration of GnRH neurons upon CCDC141 knockdown. These studies expand the clinical and genetic spectrum of IHH and also attest to the complexity of phenotype and genotype in IHH.